As políticas educacionais do governo Lula: a agenda da Secretaria de Educação Continuada, Alfabetização e da Diversidade - SECAD do Ministério da Educação - Melo, Regina Conrado (Universidade Federal de São Carlos, 2009)
The main purpose of this essay is to investigate the major factors that had influenced the creation of Secretaria de Educação Continuada, Alfabetização e da Diversidade (SECAD), one of the units of Ministério da Educação with special emphasis in the ideas. Regarding John Kingdom s theoretical framework we shall seek to identify how the ideas about inequality and diversity shared by the group that created the institution had contributed for the agenda setting of Lula s government.
Keywords: Políticas públicas; Política social; Agendas; Idéias educacionais; Diversidade; SECAD; Desigualdade; Ideas; Agenda setting; Inequality; Diversity; Educational policies; OUTROS::CIENCIAS SOCIAIS